“Estudio de procesos para la optimizacion de recursos en el área de embotellamiento de envases tipo pet de la empresa Fuentes San Felipe”. - Jacome Tonato, Dany Fabricio (2021)
This research was carried out in the company "Fuentes San Felipe", in the city of Latacunga, specifically in the facilities of the bottling plant of pet containers or also called MESAL line, which is responsible for bottling mineral water with and without gas in different presentations. The objective was to develop a study of processes, times and movement to improve the productivity of the MESAL line of the company Fuentes San Felipe. A diagnosis was made through a descriptive research to analyze and know the activities of the production workers in the Mesal line. Subsequently, the layout, process operation diagrams and flow diagrams were made. In addition, ten measurements of the times of each task were made, in order to increase the reliability of the results, they were recorded in the time study matrices, and the information was immediately processed and analyzed and the results were obtained. The proposal designed for the improvement has a positive impact on the reduction of waste, improving the behavior of the costs for this concept. In addition, the improvement proposal allows the increase of the effective production capacity, increasing the utilization, efficiency and productivity of the MESAL line.